Hypervirulent clonal complex (CC) of Listeria monocytogenes in fresh produce from urban communities - Amarasekara, Nirosha Ruwani; Swamy, Amrita Subramanya; Paudel, Sumit Kumar; Jiang, Wentao; Li, KaWang; Shen, Cangliang; Zhang, Yifan (Frontiers in Microbiology, 2024)
This study aimed to determine the prevalence and virulome of Listeria in fresh produce distributed in urban communities. A total of 432 fresh produce samples were collected from farmer's markets in Michigan and West Virginia, USA, resulting in 109 pooled samples. Listeria spp. were isolated and L. monocytogenes was subjected to genoserogrouping by PCR and genotyping by pulsed-field gel electrophoresis (PFGE). Multi-locus sequence typing (MLST) and core-genome multi-locus sequence typing (cgMLST) were conducted for clonal identification. Forty-eight of 109 samples (44.0%) were contaminated with Listeria spp. L. monocytogenes serotype 1/2a and 4b were recovered from radishes, potatoes, and romaine lettuce. Four clonal complexes (CC) were identified and included hypervirulent CC1 (ST1) and CC4 (ST219) of lineage I as well as CC7 (ST7) and CC11 (ST451) of lineage II. CC1 carried Listeria pathogenicity island LIPI-1 and LIPI-3 whereas CC4 contained LIPI-1, LIPI-3, and LIPI-4. CC7 and CC11 had LIPI-1 only. Due to previous implication in outbreaks, L. monocytogenes hypervirulent clones in fresh produce pose a public health concern in urban communities.